2021
DOI: 10.5902/1980509832130
|View full text |Cite
|
Sign up to set email alerts
|

Análise da fauna edáfica em diferentes usos do solo no Bioma Pampa

Abstract: O solo é habitado por milhares de organismos responsáveis por diversas funções no ecossistema. Entre esses organismos, destacam-se os pertencentes à fauna do solo, a qual apresenta uma grande sensibilidade às modificações realizadas no meio, podendo ser considerada como um bom bioindicador de qualidade do solo. Assim, este trabalho teve como objetivo caracterizar a distribuição da fauna edáfica em diferentes usos do solo e em diferentes épocas do ano no município de São Gabriel - RS, avaliando a sua utilização… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
7
0
4

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 13 publications
(12 citation statements)
references
References 12 publications
1
7
0
4
Order By: Relevance
“…C2 showed a statistically significant difference with the other areas and, due to the lower number of dominant groups, it obtained high equability and higher values of diversity, since this area is more structured, providing better trophic conditions and a microclimate favorable to soil macrofauna. This result supports the theory that the permanent vegetation cover of the soil in forests contributes to the conservation of edaphic biodiversity (Silva et al, 2020;Pereira, Baretta, Oliveira, Baretta, & Cardoso, 2020;Góes et al, 2021). It was also found that having a high abundance in the system did not necessarily reflect higher values of diversity, corroborating the results of Ortiz et al (2019).…”
Section: Diversity and Richnesssupporting
confidence: 84%
See 3 more Smart Citations
“…C2 showed a statistically significant difference with the other areas and, due to the lower number of dominant groups, it obtained high equability and higher values of diversity, since this area is more structured, providing better trophic conditions and a microclimate favorable to soil macrofauna. This result supports the theory that the permanent vegetation cover of the soil in forests contributes to the conservation of edaphic biodiversity (Silva et al, 2020;Pereira, Baretta, Oliveira, Baretta, & Cardoso, 2020;Góes et al, 2021). It was also found that having a high abundance in the system did not necessarily reflect higher values of diversity, corroborating the results of Ortiz et al (2019).…”
Section: Diversity and Richnesssupporting
confidence: 84%
“…These areas showed the highest numbers of Amphipoda, Araneae, Blattodea, Chilopoda, Coleoptera, Diptera, Lepidoptera, Neuroptera, Opiliones, Pseudoescorpionida, and Scorpiones. Changes in the composition of macrofauna depending on land use has been previously reported, where areas with low anthropogenic interference showed more stability in terms of soil macrofauna biodiversity when compared with areas with greater interference (Rosa et al, 2015;Silva et al, 2020;Góes et al, 2021).…”
Section: Composition Of the Soil Macrofauna Communitymentioning
confidence: 61%
See 2 more Smart Citations
“…Além disso, a composição da comunidade da macro e mesofauna de invertebrados é variável conforme o tipo e a qualidade da cobertura vegetal existente, o que reflete em condições favoráveis, como a temperatura, umidade e oferta de alimentos (GÓES et al, 2021), pois o conteúdo de matéria orgânica na superfície do solo contribui com a maior diversidade e abundância de invertebrados do solo (PESSOTO et al, 2020).…”
Section: Introductionunclassified